Probabilities : the little numbers that rule our lives - Olofsson, Peter (Hoboken : Wiley, 2014)
Praise for the First Edition"If there is anything you want to know, or remind yourself, about probabilities, then look no further than this comprehensive, yet wittily written and enjoyable, compendium of how to apply probability calculations in real-world situations."--Keith Devlin, Stanford University, National Public Radio's "Math Guy" and author of The Math Gene and The Unfinished GameFrom probable improbabilities to regular irregularities, Probabilities: The Little Numbers That Rule Our Lives, Second Edition investigates the often surprising effects of risk and chance in our lives. Featur.
Chapter 9: Faking Probabilities: Computer SimulationMahogany Dice and Modular Arithmetic; Random and Not-So-Random Digits; Number One is Number One; Is Random Really Random?; Final Word; Index; End User License Agreement.
Print version record.
Keywords: Probabilities -- Popular works; Mathematical statistics -- Popular works; Mathematics -- Miscellanea; Mathematics; Probabilities -- Popular works; Probabilities; Electronic books; Popular works